Application of Involute in the Cut Pile Mechanism of Carpet Tufting Machine - Qian Zhipeng; Meng Zhuo; Sun Yize; Ye Zhibiao (Jixie chuandong)
The pile of tufted carpet can be loop pile,cutting pile and loop cut pile. The cut pile mechanism is an important part of the carpet tufting machine,it must make sure that the actions in cut pile tufting can be happened on time. The working principle and cooperation requirement of typical cut pile mechanismare analyzed,and a new type of cut pile mechanism is designed with reference to the structure characteristics of typical cut pile mechanism and the performance advantages of involute. And then,the kinematics models of two kinds of cut pile mechanism are set up by using MATLAB- Simulink. The results show that the mechanism design of the new cut pile mechanism is reasonable. it can satisfy the technological requirements of cutting pile and is much more simple and reliable than the typical cut pile mechanism.